2010
DOI: 10.1080/13811110903479011
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Autopsy and Determination of Child Suicides: A Survey of Medical Examiners

Abstract: This study explored the decision-making processes of medical examiners in the determination of child suicide. Ninety-four medical examiners completed a survey regarding those factors considered when making a child suicide determination, sources of information used, and considerations in accident vs. suicide classifications. No significant differences between groups of respondents were observed. Well-known risk factors such as suicide notes were considered by virtually all participants, but other risk factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Underreporting may contribute differently to different suicide methods as it has been found to be associated with the coroners' suicide verdict with hanging being most likely to receive suicide verdict [18]. A study focussing on medical practitioners in USA showed that 79 % had specific factors they considered in determining accident over suicide as a cause of death in children, most commonly considered where there was no evidence of suicidal behaviour/intent, and a history of playing choking games and age (the minimum age of considering suicide verdict varied from 2 to 12 years) [19].…”
Section: Discussionmentioning
confidence: 98%
“…Underreporting may contribute differently to different suicide methods as it has been found to be associated with the coroners' suicide verdict with hanging being most likely to receive suicide verdict [18]. A study focussing on medical practitioners in USA showed that 79 % had specific factors they considered in determining accident over suicide as a cause of death in children, most commonly considered where there was no evidence of suicidal behaviour/intent, and a history of playing choking games and age (the minimum age of considering suicide verdict varied from 2 to 12 years) [19].…”
Section: Discussionmentioning
confidence: 98%
“…Suicide rates were analyzed for persons aged ≥10 years because determining suicidal intent in younger children can be difficult ( 8 ). Age-specific suicide counts were tabulated based on National Vital Statistics System coded death certificate records ( International Classification of Diseases, Tenth Revision, underlying-cause-of death codes X60–X84, Y87.0, U03).…”
Section: Methodsmentioning
confidence: 99%
“…Various researchers have shown an association between personality traits and suicide risk 20,[27][28][29]39 . Hoberman and Garfinkel 18 describes that children were more likely to be angry, nervous, anxious and impulsive before the fatal act.…”
Section: Relationship Between Mental Disorders and Suicide In Childhoodmentioning
confidence: 99%